PEMBERDAYAAN MASYARAKAT MELALUI PEMETAAN PARTISIPATIF UNTUK IDENTIFIKASI DAN PEMETAAN WILAYAH ADAT SUKU LOM DI KECAMATAN BELINYU KABUPATEN BANGKA - Iskandar Zulkarnain (Jurnal Pengabdian Kepada Masyarakat Universitas Bangka Belitung, 2014)
Empowerment of the Lom indigenous community in Belinyu District, Bangka Regency, Bangka Belitung Islands Province aims to identify social problems, potential natural resources and local wisdom that are still maintained, plan and develop the potential of natural resources and local wisdom owned by indigenous peoples for the benefit of science and welfare, and map the spatial layout of customary territories as an effort to encourage the strengthening of customary institutions. The empowerment methods used are social mapping and participatory mapping. Through both approaches, it is expected to place the community as the perpetrators of mapping their territory, as well as the determinants of their own territorial development planning. The results achieved are the identification of problems being faced in the form of the unavailability of legal legality or recognition of the existence of customary forest areas, the invasion of economic interests, and the issue of living equality with surrounding communities. Identification of potential resources including rituals, myths, potential customary forests, flora and fauna, traditional medicinal plants, and cultural potential with the presence of artifacts of ancestral heritage. Artifacts in the form of historical sites, traditional graves, sacred waterfalls, and sacred customary forests have the potential to be developed into traditional villages as natural and cultural tourist destination areas in the future. Achieving this all depends on the dynamics of the role and function of the customary institutions of the Lom community in mobilizing the power of social capital.